PWE-101 Patient'S Awareness of the Need for Vaccinations Whilst on Immunosuppressive Therapy. (4th June 2013) - Widlak, M; Matharu, R; Elzubeir, A; Slater, J; Wood, L; Silva, S De
Abstract : Introduction: With the ever increasing use of immunosuppressive therapy for the management of inflammatory bowel disease (IBD) patients are being exposed to infections which can be prevented by vaccinations administered prior to or during therapy. The European Crohn's and Colitis Organisation guidelines currently recommend that IBD patients who receive immunosuppressive medications should be vaccinated yearly with the influenza vaccine and a pneumococcal vaccination 3–5 yearly. Methods: An audit was carried out within our department to assess our patient's knowledge and uptake of such vaccines. Patients with Inflammatory Bowel Disease were identified from an established data base and those receiving immunosuppressive therapy were invited to complete a questionnaire. Data gathered included age, gender, current treatment and awareness of the need for vaccinations. We also gathered data on the number of patients already vaccinated. Results: A cohort of 88 patients on immmunosuppressive therapy was analysed. 61% of patients were female and 39% male. Patients ranged between 16–21 years (11%), 22–30 years (18%), 31–50 years (40%), 51–70 years (24%) and above 70 (7%). 59 (67%) patients had Crohn's disease, 26 (29.5%) ulcerative colitis and 3 of them (3.5%) had indeterminate colitis. The majority of patients received immunomodulators including Azathioprine or Mycophenolate (n = 48, 54%). 13 (15%) were treated with biologics alone (Infliximab or Adalimumab), 21 (24%) with combination of biologics and immunomodulators and 6 patients (7%) received immunomodulators with a reducing dose of steroids. 77% of patients were aware of recommended vaccinations but as many as 23% were not. 42% were aware of the importance of receiving dual vaccinations, 35% were only aware of the need for either the influenza or pneumococcal vaccine, with 23% unaware of the need for either. In this cohort 54 (61%) patients had already had or were planning to have the influenza vaccine this year. Patients between the ages of 31–50 years had the highest awareness of the recommended vaccines (86%), with the majority of uptake of vaccines seen in the 31–50 year group (63%). Unfortunately 39% of patients were not receiving recommended vaccinations with more than half (56%) of patients being unaware of the need to avoid live vaccinations. Conclusion: Our data suggest that a significant proportion of patients within our cohort are still not receiving vaccinations that were recommended to them. Although 77% were aware of a form of recommended vaccine, 39% were not receiving them. Wider education of our IBD patients as well as their primary care doctors should be implemented to increase awareness and uptake of vaccines to provide adequate protection to this vulnerable group. Disclosure of Interest: None Declared.